Kesesuaian Diagnosis Klinis dan Hasil Pemeriksaan Histopatologi Psoriasis Vulgaris - Puguh Riyanto; Felicia Yora Afrilia Putri; Myrna Adiwijaya; Rima Adjani Nugroho; Hani Nur Rahmawati Purwanto (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Psoriasis is a chronic inflammatory disease that attacks the skin and can occur at any age with various clinical variations. The diagnosis is generally made clinically, but in atypical cases a biopsy is required for confirmation. The combination of clinical and histopathological examination provides more accurate diagnosis results. This study aims to assess the suitability of clinical diagnosis and histopathological examination results in psoriasis vulgaris in Semarang Regency. This cross-sectional observational study was conducted by the department of dermatology, venereology and aesthetics at Diponegoro University. A total of 10 samples were clinically diagnosed as psoriasis vulgaris or other morphological types of psoriasis vulgaris at a Dermatology Polyclinic in Semarang Regency, over a period of 2 years. The clinical manifestations of 10 cases with a clinical diagnosis of psoriasis vulgaris assessed from the typical predilection and the presence of scaly plaques tended to be consistent with the histopathological diagnosis but were not statistically significant. Concordance between clinical diagnosis and histopathological diagnosis was observed in 8 (80%) cases and discordance in 2 (20%) cases. Based on the research results, it can be concluded that there is a high level of agreement (80%) between clinical diagnosis and histopathological features in cases of psoriasis vulgaris.